The use of games to enrich the learning of english language vocabulary among ninthgrade students at unidad educativa José ángel Palacio in the city of Loja during the 2018-2019 school year - Correa Criollo, Pablo Israel (2019)
The main objective of the research was to use games to enrich the learning of English language vocabulary among ninth-grade students at Unidad Educativa José Angel Palacio in the city of Loja during the 2018-2019 school year. The methods used were scientific, descriptive, statistical, and synthetic-analytical, which served to collect information, describe the stages of study, interpret and represent the results obtained in the research. Data was collected through tests and questionnaires applied to 26 students. Likewise, observation sheets and field notes were used to record the students’ attitudes during the intervention plan. Students increased their vocabulary notably through the use of games in five indicators: nouns, verbs, adjectives, quantifiers, and idioms. In conclusion, the research demonstrated that the application of games helped students to overcome their difficulties in the learning of vocabulary, promoted cooperation, and motivated them to participate more actively in the classroom.